The growth of youth culture made possible mechanisms of ensuring strategic reading in Uzbekistan - Abdulvahid Habibullayevich Abdulazizov (Periodica Journal, 2025)
The article describes the author's socio-philosophical point of view about the strategic mechanisms that ensure the rise of the reading culture, which is considered relevant in today's society. An attempt was made to objectively analyze the state of the processes of the role of the library and new information technologies in the development of the reading culture of young people. Emphasizing the relevance of the formation and development of the reading culture among young people, it is concluded that the phenomenon of reading is one of the least studied areas, especially the question of the formation of the reading culture and thinking of students.
Keywords: bound book; book printing products; advertising